Porous high-temperature-resistant antioxidant composite ceramic and preparation method thereof

Through the modified polyborosilazane precursor of multiple transition metal precursors, high entropy carbide/silico boron carbon-nitrogen composite ceramics are prepared by in-situ carbon thermal reduction and solid solution reaction, and the structural failure of porous SiBCN ceramics at high temperatures is solved and The problem of deterioration of performance has achieved significant improvement in the high-temperature stability and oxidation resistance of ceramics, meeting the application needs of ultra-high temperature porous ceramic materials.

CN119118674APending Publication Date: 2024-12-13TIANJIN UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411254844.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-09
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

Existing porous SiBCN ceramics tend to crystallize and decompose under high temperature conditions, and have poor oxidation properties, resulting in structural damage and deterioration of performance, making it difficult to meet the needs of ultra-high temperature heat insulation and catalysis.

Method used

Using a multivariate transition metal precursor to modify the polyborsilazane precursor, high entropy carbide/silico boron carbon-nitrogen composite ceramics (HEC/SiBCN) are prepared at a lower temperature through in-situ carbon thermal reduction and solid solution reactions to achieve The uniform mixing and structural regulation of the two atomic levels is improved, and the high temperature stability and oxidation resistance of the ceramic are improved.

Benefits of technology

The prepared porous HEC/SiBCN ceramics have low density, high strength, low thermal conductivity and excellent high-temperature oxidation resistance. They can maintain stability in an inert environment of 1800℃ and an air environment of 1400℃, meeting high-temperature thermal protection, electromagnetic shielding and Application requirements in the fields of catalytic support and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119118674A_ABST
    Figure CN119118674A_ABST
Patent Text Reader

Abstract

The invention relates to a porous high-temperature-resistant antioxidant high-entropy carbide / silicon-boron-carbon-nitrogen composite ceramic and a preparation method thereof. Polyborosilazane is used as a ceramic precursor, divinylbenzene is used as a cross-linking agent, a high-entropy carbide precursor is used as a modifier, and the porous high-entropy carbide / silicon-boron-carbon-nitrogen composite ceramic is obtained through solvothermal reaction, drying and high-temperature pyrolysis. The porous ceramic has the advantages of high porosity, easiness in adjustment, low heat conductivity, high strength and the like; meanwhile, a high-entropy carbide phase is generated in situ in the porous ceramic by utilizing a carbon thermal reduction reaction in a pyrolysis process, so that the high-temperature stability of the porous silicon-boron-carbon-nitrogen ceramic is greatly improved, and high temperature resistance in an inert atmosphere of 1800 DEG C and oxidation resistance in air of 1400 DEG C are realized. The porous ceramic can be used as materials such as heat insulation / protection, electromagnetic shielding, hot gas filtration and catalytic carriers to be applied to high-temperature fields such as traffic, chemical engineering, energy, aerospace and the like, and meets the requirements of different fields on ultrahigh-temperature porous ceramic materials.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to porous ceramic materials used in the fields of transportation, chemical industry, energy, aerospace, etc., including high-temperature thermal insulation / thermal protection, high-temperature electromagnetic shielding, hot gas filtration, catalytic carrier, etc. In particular, it relates to a porous high-temperature resistant and anti-oxidation composite ceramic and a preparation method thereof. Background Art

[0002] Porous ceramic materials have the characteristics of low density, large specific surface area, high toughness, strong thermal shock resistance, low thermal conductivity, and excellent high-temperature stability. They can be used in high-temperature thermal insulation / thermal protection, electromagnetic shielding, hot gas filtration, catalytic carriers, sewage treatment and other fields. However, with the development of technology and market demand, especially the huge demand in extreme (ultra) high temperature fields, such as rocket nozzles, next-generation nuclear reactors, engines, and leading edges of hypersonic vehicles, people have put forward higher requirements for porous thermal structural materials, requiring porous ceramic materials to have better high temperature resistance, oxidation resistance, ablation resistance, and thermal shock resistance. Porous oxide ceramics have a low melting point and are difficult to be used in the field of ultra-high temperature thermal insulation; while non-oxide porous ceramics have high strength, high hardness, excellent oxidation resistance, and excellent thermal and chemical stability, but are subject to complex preparation technology, such as the addition of sintering aids, excessively high sintering temperatures, and difficult processing, which also hinders their application and development. Therefore, it is of great significance to develop a new type of easy-to-prepare high-temperature resistant and oxidation-resistant porous non-oxide ceramic.

[0003] Polymer-derived ceramics (PDCs) are synthesized by chemical methods from precursor oligomers or polymers, and then molded and pyrolyzed to obtain ceramics. They have the advantages of molecular designability, good processability, and machinability. Among many precursor ceramics, PDC-SiBCN ceramics have a long-range disordered amorphous structure and strong covalent bonding to form a rigid network. They show excellent (ultra) high temperature stability in an inert atmosphere up to 2000°C, good oxidation resistance in air at 1600°C, and excellent high temperature creep resistance (the creep strain is only 0.25% at 1400°C) (Adv. Eng. Mater. 2018, 20, 1800360). These characteristics make SiBCN ceramics an ideal ultra-high temperature porous material. However, at high temperatures, driven by thermodynamics, SiBCN ceramics will gradually transform to local order, accompanied by the structural evolution of nucleation-crystallization and carbon thermal reduction reaction, resulting in structural destruction and performance degradation. The presence of porous structure will further accelerate the high temperature reaction of SiBCN ceramics, further reducing the use temperature and service life of SiBCN ceramic products. Therefore, it is very important to improve the crystallization resistance, high temperature decomposition resistance and oxidation resistance of porous SiBCN ceramics, and then expand its application in high temperature thermal protection, catalysis, filtration and other fields.

[0004] Modification with metal elements is a method to improve the high-temperature stability of SiBCN ceramics. At present, there have been reports on the modification of SiBCN porous ceramics with a single metal element. For example, Sun et al. (ACS Appl Mater Interfaces 2023, 15, 12221) prepared TiCN / SiBCN aerogel by modifying polyborosilazane with tetrabutyl titanate. This aerogel can resist thermal decomposition and crystallization to 1800°C in an argon atmosphere, but its oxidation resistance is extremely poor, and a large amount of mass loss occurs during 600°C-800°C, resulting in structural collapse, performance deterioration, and inducing safety failures, limiting its application under high temperature conditions. Therefore, while improving the high-temperature stability of porous SiBCN ceramics, the improvement of antioxidant properties cannot be ignored. However, there are currently no public reports on the research on SiBCN ceramics modified with multi-transition metal elements. It is of great significance to introduce a high entropy phase into porous SiBCN ceramics to develop new SiBCN-based porous ceramics with higher comprehensive performance.

[0005] For multi-component ceramic materials, ceramic materials composed of five or more metal cations in equal or nearly equal amounts, their S config ≥1.16R, can be called high entropy ceramic material. With the continuous improvement and development of high entropy material research, the definition of high entropy material has been expanded. At present, the four-component equal amount or nearly equal amount system is also called high entropy system (Ceram Int 2020,46,15104). High entropy carbide (HEC) exhibits excellent physical and chemical properties such as high hardness, elastic modulus, excellent oxidation resistance and stability, and low thermal conductivity (J EurCeram Soc 2022,40,2746), which has attracted great attention from domestic and foreign researchers. At present, porous high entropy carbide ceramics are usually prepared by powder sintering and adding foaming agent (J Mater Sci Technol 2022,119,20), but this method has problems such as too high sintering temperature, uneven composition, and addition of sintering aids. If the above traditional preparation method is used, it is difficult to evenly disperse the carbide powder into the SiBCN precursor solution, which affects the molding and performance of the porous ceramic material. The present invention provides a method for preparing high entropy carbide / silicon boron carbon nitrogen composite ceramic material (HEC / SiBCN) by in-situ reaction, which realizes uniform mixing of the two at the atomic level and has the characteristics of adjustable structure and excellent high-temperature performance. The oxidation resistance can reach up to 1400°C and the thermal structure stability can reach up to 1800°C. It can be applied to porous ceramic fields such as high-temperature thermal insulation / thermal protection, high-temperature electromagnetic shielding, hot gas filtration, and catalytic carriers. Summary of the invention

[0006] In view of the problem that porous SiBCN ceramic materials tend to crystallize, decompose, and have poor oxidizability under high temperature conditions, resulting in structural damage and deterioration of performance, the present invention provides a method for preparing porous high-temperature resistant and antioxidant HEC / SiBCN composite ceramics. Specifically, a method of modifying a polyborosilazane precursor with a multi-element transition metal precursor is adopted, and porous HEC / SiBCN ceramics are prepared under relatively low temperature conditions by in-situ carbon thermal reduction and solution reaction. This porous HEC / SiBCN ceramic has the advantages of low density, high strength, low thermal conductivity, excellent high-temperature stability and high-temperature oxidation resistance, and especially meets the requirements for a new generation of thermal insulation materials in the future field of high-temperature thermal protection.

[0007] The specific technical solutions of the present invention are as follows:

[0008] A porous high temperature resistant and oxidation resistant composite ceramic, wherein the composite ceramic is a high entropy carbide / silicon boron carbon nitrogen composite ceramic.

[0009] The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic of the present invention comprises the following steps:

[0010] 1) Using a variety of transition metal inorganic salts / organic complexes as metal precursors and dissolving them in an organic solvent for reaction, a high entropy carbide precursor is obtained through hydrolysis and condensation reactions;

[0011] 2) using polyborosilazane as a ceramic precursor, divinylbenzene as a crosslinking agent, and a high entropy carbide precursor as a modifier, dissolving them in an organic solution, and fully mixing them to obtain a transparent solution; using a solvent thermal reaction to form a wet gel;

[0012] 3) obtaining a dry gel by freeze drying;

[0013] 4) Porous high entropy carbide / silicon boron carbon nitrogen composite ceramics are obtained by high temperature pyrolysis.

[0014] In the step 1), the metal precursor is a metal alkoxide, a metal acetylacetonate complex or a metal inorganic salt.

[0015] The metal elements in the high entropy carbide precursor in step 1) include titanium, zirconium, hafnium, tantalum, niobium, tungsten, molybdenum, yttrium, chromium, and vanadium, and 4 to 6 of them are selected.

[0016] The organic solvent in step 1) includes n-butanol, toluene or acetylacetone.

[0017] In the step 1), a plurality of transition metal precursors are added to an organic solvent and reacted at 100-180° C., and then the solvent is removed by distillation.

[0018] In the step 2), the mass ratio of polyborosilazane to high entropy carbide precursor is 1:(0.5-3).

[0019] In the step 2), the mass ratio of polyborosilazane to divinylbenzene is 1:(0-2).

[0020] The solvent thermal temperature in step 2) is 100-200° C.; the organic solvent includes cyclohexane, acetylacetone, and N,N-dimethylformamide.

[0021] In the step 3), the wet gel obtained in the step 2) is dried to obtain a dry gel; the drying method is vacuum freeze drying or supercritical drying.

[0022] In the step 4), the pyrolysis temperature is 1400-1800° C., and the pyrolysis is carried out under vacuum conditions, or under a protective atmosphere, wherein the protective atmosphere is argon or nitrogen.

[0023] The present invention uses a variety of transition metal inorganic salts / organic complexes as metal precursors, and obtains a high entropy carbide (HEC) precursor through hydrolysis and condensation reactions. Then, polyborosilazane (PBSZ) is used as a ceramic precursor, divinylbenzene (DVB) is used as a crosslinking agent, and the HEC precursor is a high entropy carbide precursor, which are dissolved in an organic solution and fully mixed to obtain a transparent solution. Then, a solvent thermal reaction is used to form a wet gel, and a dry gel is obtained after solvent replacement and freeze drying, and finally a porous HEC / SiBCN composite ceramic is obtained by high-temperature pyrolysis. All steps are carried out in an anhydrous and oxygen-free inert environment.

[0024] The present invention provides a method for preparing HEC / SiBCN porous ceramics by in-situ carbothermal reduction and solid solution reaction, that is, using multi-element transition metal elements to modify PBSZ as a precursor, using the highly active free carbon formed during the pyrolysis process to undergo a carbothermal reduction reaction with the metal precursor to form a metal carbide, and further undergoing a solid solution reaction to form a high entropy carbide crystal phase. This method is simple in process, and the structure, composition, and performance of the obtained HEC / SiBCN porous ceramics are easy to control, which greatly improves the upper limit of the operating temperature and reliability of SiBCN porous ceramics, and expands its application range in extreme fields such as energy, aerospace, and military industry.

[0025] The HEC / SiBCN porous ceramics obtained by the present invention have an adjustable high porosity (58.9%-75.1%), a low thermal conductivity (0.054-0.075Wm -1 K -1 ), high strength (~35MPa) and excellent high temperature stability and oxidation resistance (inert atmosphere can be stable to 1800℃, air atmosphere can be stable to 1400℃, which meets the requirements of ultra-high temperature porous ceramic materials in the fields of transportation, chemical industry, energy, aerospace, etc. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 13 is the XRD spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 1.

[0027] Figure 2 This is the TEM spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 1.

[0028] Figure 3 This is the SEM spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 1.

[0029] Figure 4 This is a SEM spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 1 after heat treatment at 1800°C for 2h.

[0030] Figure 5 This is the TG spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 1.

[0031] Figure 6 This is the XRD spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 2.

[0032] Figure 7 This is the XRD spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 3.

[0033] Figure 8 This is the XRD spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 5.

[0034] Fig. 9 This is the SEM spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 5.

[0035] Fig.10 This is the XRD spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 8.

[0036] Fig.11 : is the XRD spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 9.

[0037] Fig.12 This is the SEM spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 9.

[0038] Fig.13 This is the SEM spectrum of the porous HEC / SiBCN composite ceramic prepared in Example 11. DETAILED DESCRIPTION

[0039] The present invention is further described in detail below in conjunction with specific examples, which are intended to explain the present invention rather than to limit it. The abbreviations in the examples have the following meanings: high entropy carbide (HEC), polyborosilazane (PBSZ), divinylbenzene (DVB), high entropy carbide / silicon boron carbon nitrogen (HEC / SiBCN).

[0040] Example 1

[0041] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were dissolved in 25.63 g of n-butanol, and the mixture was in an oil bath at 140° C. for 1 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0042] 2) Preparation of wet gel: PBSZ:HEC is 1:1, PBSZ:DVB is 1:1, 1g of PBSZ, 1g of metal precursor solution and 1g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 150°C for 20 hours to obtain a wet gel.

[0043] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at 0° C. for 48 h to obtain a dry gel.

[0044] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1600° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0045] The microstructure and phase composition of porous HEC / SiBCN ceramics were analyzed by scanning electron microscopy (SEM, s4800, Japan), transmission electron microscopy (TEM, JEOL-200CX, Japan) and X-ray diffractometer (XRD, D8 advanced, Germany). The density of porous HEC / SiBCN ceramics was calculated by Archimedes drainage method. The compressive strength and thermal conductivity of porous HEC / SiBCN ceramics were tested by universal testing machine (LD24.204, China) and thermal constant analyzer (TC3000, China). The obtained porous HEC / SiBCN ceramics were heat treated in a high-temperature furnace at 1800℃ in argon atmosphere for 2h, and their high-temperature stability was evaluated by weight loss, linear shrinkage, density and microstructural changes after heat treatment. The anti-oxidation properties of porous HEC / SiBCN in air atmosphere at 1400℃ were evaluated by thermogravimetric analyzer (TG, Netzsch STA449F3, Germany).

[0046] The XRD results show that (Ti0.25 Zr 0.25 Hf 0.25 Ta 0.25 )C(HEC) crystal phase is generated in situ in the SiBCN matrix, such as Figure 1 As shown in Figure 2, HEC / SiBCN composite ceramics are formed. TEM observation shows that HEC crystals are uniformly distributed in the SiBCN matrix. Figure 2 As shown. SEM observations show that the porous HEC / SiBCN ceramics have a three-dimensional nanoporous network structure, as shown in Figure 3 shown.

[0047] The test results show that the porous ceramic has a low density of 0.874 g / cm 3 , low thermal conductivity 0.054Wm -1 K -1 , high compressive strength of 35MPa, meeting the needs of practical applications. After further heat treatment at 1800℃ for 2h, the weight loss of HEC / SiBCN composite ceramic aerogel was only 4.8wt%, and the linear shrinkage was only 5.4%. After heat treatment, the three-dimensional network porous structure was still highly maintained without damage at the microscopic level. Figure 4 As shown, it has excellent high temperature resistance. When heat treated in air, the mass loss starts at about 1000℃, and the thermal weight loss is only 9.4% at 1400℃. Figure 5 As shown, it exhibits excellent antioxidant properties.

[0048] Example 2

[0049] 1) Preparation of HEC precursor solution: 2.44 g of zirconium acetylacetonate, 2.88 g of hafnium acetylacetonate, 1.7 g of tetrabutyl titanate, and 2.04 g of tantalum ethoxide were weighed and dissolved in 51.26 g of n-butanol. After being in an oil bath at 140° C. for 1 h, rotary evaporation was performed in a water bath at 70° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0050] 2) Preparation of wet gel: PBSZ:HEC is 1:0.5, PBSZ:DVB is 1:1, 1.2g of PBSZ, 0.6g of metal precursor solution and 1.2g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 120℃ for 20h to obtain a wet gel.

[0051] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 60 min, and then transferred to a freeze dryer and dried at 0° C. for 48 h to obtain a dry gel.

[0052] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1400° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0053] The XRD results show that (Ti 0.25 Zr 0.25 Hf 0.25 Ta 0.25 )C(HEC) crystal phase is generated in situ in the SiBCN matrix, such as Figure 6 As shown, a HEC / SiBCN composite ceramic is formed. The porous ceramic has a mass of 0.759 g / cm 3 , 65.97% porosity, low thermal conductivity of 0.048Wm -1 K -1 , meeting the needs of practical applications. After further heat treatment at 1800℃ for 2h, the weight loss of HEC / SiBCN composite ceramics was only 7.9wt%, the linear shrinkage was only 5.1%, the high compressive strength was 12MPa, and it had excellent thermal stability.

[0054] Example 3

[0055] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were dissolved in 25.63 g of n-butanol, and the mixture was in an oil bath at 140° C. for 1 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0056] 2) Preparation of wet gel: PBSZ:HEC is 1:2, PBSZ:DVB is 1:1, 0.75g of PBSZ, 1.5g of metal precursor solution and 0.75g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 180℃ for 20h to obtain a wet gel.

[0057] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at 0° C. for 48 h to obtain a dry gel.

[0058] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1800° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0059] The XRD results show that (Ti 0.25 Zr 0.25 Hf 0.25 Ta 0.25 )C(HEC) crystal phase is generated in situ in the SiBCN matrix, such as Figure 7 As shown, a HEC / SiBCN composite ceramic is formed. The porous ceramic is measured to have a low thermal conductivity of 0.061 Wm -1 K -1 , meeting the needs of practical applications. After further heat treatment at 1800℃ for 2h, the weight loss of HEC / SiBCN composite ceramics was only 2.75wt%, and the linear shrinkage was only 4.9%, showing excellent high temperature resistance.

[0060] Example 4

[0061] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were weighed and dissolved in 25.63% toluene. After being in an oil bath at 140° C. for 1 h, rotary evaporation was performed in a water bath at 70° C. for 1.2 h to obtain a viscous yellow transparent HEC precursor solution.

[0062] 2) Preparation of wet gel: PBSZ:HEC is 1:0.5, PBSZ:DVB is 1:1, 1g of PBSZ, 1g of metal precursor solution and 1g of DVB are added to 17g of N,N-dimethylformamide under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 100°C for 24h to obtain a wet gel.

[0063] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at -10°C for 24 h to obtain a dry gel.

[0064] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1600° C. for 1 h under vacuum conditions to obtain porous HEC / SiBCN ceramics.

[0065] Example 5

[0066] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were weighed and dissolved in 25.63 g of n-butanol. After being in an oil bath at 160° C. for 1 h, rotary evaporation was performed in a water bath at 80° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0067] 2) Preparation of wet gel: PBSZ:HEC is 1:3, PBSZ:DVB is 1:1, 0.6g of PBSZ, 1.8g of metal precursor solution and 0.6g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 200℃ for 15h to obtain a wet gel.

[0068] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at 0° C. for 48 h to obtain a dry gel.

[0069] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1800° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0070] The XRD results show that (Ti 0.25 Zr 0.25 Hf 0.25 Ta 0.25 )C(HEC) is formed in situ in the SiBCN matrix, such as Figure 8 As shown. SEM observation showed that HEC / SiBCN ceramics have a three-dimensional nanoporous network structure, as shown Fig. 9 As shown, a porous HEC / SiBCN composite ceramic is formed.

[0071] Example 6

[0072] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were weighed and dissolved in 25.63% toluene. After being in an oil bath at 120° C. for 1.5 h, rotary evaporation was performed in a water bath at 60° C. for 1.5 h to obtain a viscous yellow transparent HEC precursor solution.

[0073] 2) Preparation of wet gel: PBSZ:HEC is 1:1, PBSZ:DVB is 1:0, 3g of PBSZ, 3g of metal precursor solution and 0g of DVB are added to 34g of N,N-dimethylformamide under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 150°C for 20h to obtain a wet gel.

[0074] 3) Drying the wet gel: The wet gel obtained in step 2) is subjected to CO2 supercritical drying to obtain a dry gel.

[0075] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) was placed in a tubular furnace and pyrolyzed at 1800° C. for 1.5 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0076] Example 7

[0077] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were dissolved in 25.63 g of acetylacetone, and the mixture was incubated in an oil bath at 100° C. for 2 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0078] 2) Preparation of wet gel: PBSZ:HEC is 1:1, PBSZ:DVB is 1:2, 0.75g of PBSZ, 0.75g of metal precursor solution and 1.5g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 100℃ for 30h to obtain a wet gel.

[0079] 3) Drying the wet gel: The wet gel obtained in step 2) is subjected to CO2 supercritical drying to obtain a dry gel.

[0080] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1600° C. for 3 h under nitrogen protection to obtain porous HEC / SiBCN ceramics.

[0081] Example 8

[0082] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, and 1.02 g of tantalum ethoxide were dissolved in 25.63 g of n-butanol, and the mixture was in an oil bath at 140° C. for 1 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0083] 2) Preparation of wet gel: PBSZ:HEC is 1:2, PBSZ:DVB is 1:2, 0.6g PBSZ, 1.2g metal precursor solution and 1.2g DVB are added to 17g cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 150℃ for 20h to obtain a wet gel.

[0084] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at 0° C. for 48 h to obtain a dry gel.

[0085] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1600° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0086] The XRD results show that (Ti 0.25 Zr 0.25 Hf0.25 Ta 0.25 )C(HEC) is formed in situ in the SiBCN matrix, such as Fig.10 As shown, a porous HEC / SiBCN composite ceramic is formed.

[0087] Example 9

[0088] 1) Preparation of HEC precursor solution: 1.22 g of zirconium acetylacetonate, 1.44 g of hafnium acetylacetonate, 0.85 g of tetrabutyl titanate, 1.02 g of tantalum ethoxide, and 0.80 g of niobium ethoxide were dissolved in 30.2 g of n-butanol, and the mixture was in an oil bath at 140° C. for 1 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous yellow transparent HEC precursor solution.

[0089] 2) Preparation of wet gel: PBSZ:HEC is 1:1, PBSZ:DVB is 1:1, 1g of PBSZ, 1g of metal precursor solution and 1g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and magnetic stirring is used to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 180°C for 20 hours to obtain a wet gel.

[0090] 3) Drying the wet gel: The wet gel obtained in step 2) is subjected to CO2 supercritical drying to obtain a dry gel.

[0091] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1800° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0092] The XRD results show that (Ti 0.2 Zr 0.2 Hf 0.2 Ta 0.2 Nb 0.2 )C is formed in situ in the SiBCN matrix, such as Fig.11 As shown in Figure 2, the porous HEC / SiBCN ceramics have a three-dimensional nanoporous network structure as observed by SEM. Fig.12 As shown, a porous HEC / SiBCN composite ceramic is formed.

[0093] Example 10

[0094] 1) Preparation of HEC precursor solution: 0.82 g of molybdenum acetylacetonate, 0.88 g of chromium acetylacetonate, 0.85 g of tetrabutyl titanate, 1.02 g of tantalum ethoxide, and 0.80 g of niobium ethoxide were dissolved in 24.76 g of toluene, and the mixture was incubated in an oil bath at 100° C. for 1.5 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous transparent HEC precursor solution.

[0095] 2) Preparation of wet gel: PBSZ:HEC is 1:1, PBSZ:DVB is 1:1, 1g of PBSZ, 1g of metal precursor solution and 1g of DVB are added to 17g of acetylacetone under the protection of flowing inert gas, and magnetic stirring is used to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 180°C for 20 hours to obtain a wet gel.

[0096] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at 0° C. for 24 h to obtain a dry gel.

[0097] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1800° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0098] Embodiment 11

[0099] 1) Preparation of HEC precursor solution: 0.85 g of tetrabutyl titanate, 1.02 g of tantalum ethoxide, 0.64 g of tungsten chloride, 1.01 g of yttrium acetylacetonate hydrate, and 0.66 g of vanadium oxide acetylacetonate were dissolved in 23.69 g of n-butanol, and the mixture was in an oil bath at 180° C. for 1 h, and then rotary evaporated in a water bath at 80° C. for 1 h to obtain a viscous, transparent HEC precursor solution.

[0100] 2) Preparation of wet gel: PBSZ:HEC is 1:1, PBSZ:DVB is 1:1, 1g of PBSZ, 1g of metal precursor solution and 1g of DVB are added to 17g of cyclohexane under the protection of flowing inert gas, and stirred with magnetic stirring to obtain a uniform solution. The obtained solution is transferred to a hydrothermal kettle and placed in an oven at 200℃ for 20h to obtain a wet gel.

[0101] 3) Drying of wet gel: The wet gel obtained in step 2) was placed in a refrigerator and frozen for 30 min, and then transferred to a freeze dryer and dried at -10°C for 48 h to obtain a dry gel.

[0102] 4) Pyrolysis of dry gel: The dry gel obtained in step 3) is placed in a tubular furnace and pyrolyzed at 1800° C. for 2 h under argon protection to obtain porous HEC / SiBCN ceramics.

[0103] like Fig.13 As shown in Figure 2, the porous HEC / SiBCN ceramics were observed to have a three-dimensional nanoporous structure with a density of 0.268 g / cm 3 , the porosity reaches 89%, meeting the actual application needs.

[0104] The present invention relates to a method for preparing a high temperature resistant and oxidation resistant porous HEC / SiBCN composite ceramic. Specifically, a method of modifying a polyborosilazane precursor with a multi-element transition metal precursor is adopted, and porous HEC / SiBCN ceramics are prepared under relatively low temperature conditions by in-situ carbon thermal reduction and solution reaction. This porous HEC / SiBCN ceramic has low density, low thermal conductivity and high compressive strength, and can maintain structural stability in an inert environment up to 1800°C and an air environment at 1400°C, as well as good thermal and mechanical properties. The present invention provides a method for preparing a high temperature resistant porous SiBCN ceramic material, which improves the upper temperature resistance limit of the porous SiBCN material, broadens its application range in extreme environments, and especially meets the requirements for a new generation of thermal insulation materials in the future field of high temperature thermal protection.

[0105] By adjusting the process parameters described in the present invention, the preparation of porous HEC / SiBCN composite ceramics can be achieved, and the performance is basically consistent with that of the example. The above description is only a preferred embodiment of the present application and is not intended to limit the present application. For those skilled in the art, the present application may have various changes and variations. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application shall be included in the scope of protection of the present application.

Claims

1. A porous high temperature resistant and anti-oxidation composite ceramic, Its characteristics are: The composite ceramic is a high entropy carbide / silicon boron carbon nitrogen composite ceramic.

2. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 1, Its characteristics are: The steps include: 1) Using a variety of transition metal inorganic salts / organic complexes as metal precursors and dissolving them in an organic solvent for reaction, a high entropy carbide precursor is obtained through hydrolysis and condensation reactions; 2) using polyborosilazane as a ceramic precursor, divinylbenzene as a crosslinking agent, and a high entropy carbide precursor as a modifier, dissolving them in an organic solution, and fully mixing them to obtain a transparent solution; using a solvent thermal reaction to form a wet gel; 3) obtaining a dry gel by freeze drying; 4) Porous high entropy carbide / silicon boron carbon nitrogen composite ceramics are obtained by high temperature pyrolysis.

3. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: In the step 1), the metal precursor is a metal alkoxide, a metal acetylacetonate complex or a metal inorganic salt.

4. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: The metal elements in the high entropy carbide precursor in step 1) include titanium, zirconium, hafnium, tantalum, niobium, tungsten, molybdenum, yttrium, chromium, and vanadium, and 4 to 6 of them are selected.

5. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: The organic solvent in step 1) includes n-butanol, toluene or acetylacetone.

6. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: In the step 2), the mass ratio of polyborosilazane to high entropy carbide precursor is 1:(0.5-3).

7. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: In the step 2), the mass ratio of polyborosilazane to divinylbenzene is 1:(0-2).

8. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: The solvent thermal temperature in step 2) is 100-200° C.; the organic solvent includes cyclohexane, acetylacetone, and N,N-dimethylformamide.

9. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: In the step 3), the wet gel obtained in the step 2) is dried to obtain a dry gel; the drying method is vacuum freeze drying or supercritical drying.

10. The method for preparing the porous high temperature resistant and oxidation resistant composite ceramic according to claim 2, Its characteristics are: In the step 4), the pyrolysis temperature is 1400-1800° C., and the pyrolysis is carried out under vacuum conditions, or under a protective atmosphere, wherein the protective atmosphere is argon or nitrogen.

Citation Information

Patent Citations

  • Multi-component carbide / silicon carbide nano composite ceramic and preparation method thereof

    CN115180950A

  • High-temperature-resistant transition metal carbide (nitride) / silicon-boron-carbon-nitrogen composite ceramic aerogel and preparation method thereof

    CN116023150A